2009
DOI: 10.3998/ark.5550190.0009.h13
|View full text |Cite
|
Sign up to set email alerts
|

Improving enantioselectivity via rationally tuning electronic effect of catalysts in the organocatalytic asymmetric aldol reaction

Abstract: Both steric repulsion and electronic effect govern the stereoselectivity in asymmetric catalysis. Rationally electronic-tuned N-(2-hydroxylphenyl)-(S)-prolinamide derived catalysts were designed, synthesized, and evaluated in the asymmetric aldol reaction. The results indicate that the enantiomeric ratios of products correlate well with the Hammett constants, which confirms that the enantioselectivity was improved via rationally tuning catalyst electronic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Remote substitution is an important way to modify the structures of proline based organocatalysts. ,, And several previous studies indicated that the enantioselectivity can be tuned by the electronic effect of the remote substituents at amide nitrogen. , To depict a full image of the remote-substituent effect, we calculate the acidities of series of p -substituted ( S )-proline amide and its derivatives, including N-phenyl prolinamide, N-phenyl proline thioamide, and N-phenylsulfonyl prolinamide. The results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote substitution is an important way to modify the structures of proline based organocatalysts. ,, And several previous studies indicated that the enantioselectivity can be tuned by the electronic effect of the remote substituents at amide nitrogen. , To depict a full image of the remote-substituent effect, we calculate the acidities of series of p -substituted ( S )-proline amide and its derivatives, including N-phenyl prolinamide, N-phenyl proline thioamide, and N-phenylsulfonyl prolinamide. The results are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although p K a values of a lot of organic compounds in water are also available, the leveling effect of water makes it difficult or impossible to directly measure the acidity constants above p K HA = 12. ,, And for weaker acids in aqueous solution, p K a values are usually determined by extrapolation or kinetic measurement that may be complicated by ion-paring and aggregation effects . Thus most of the p K a values of amide and its derivatives available in water are those having relative strong acidities like thioamide and sulfonamide. , Moreover, not only is DMSO itself a widely used solvent in organocatalysis, ,,, but also the linear relationships between the acidities in DMSO and the acidities in some other solvents, such as THF, MeCN, and DMF, , are well studied. Therefore p K a values in DMSO can also serve as a reference for the organocatalysts used in these solvents.…”
Section: Introductionmentioning
confidence: 99%
“…A process where catalyst acidity controls enantioselectivity is revealed. Since our initial report of a direct correlation between catalyst acidity and enantioselectivity, examples of similar trends in other hydrogen bond-catalyzed reactions have emerged, , implying this effect is not unique to our system. However, ideal catalyst acidity is likely to differ depending on the specific reaction of interest, as the role of the catalyst is to stabilize the transition state more than the bound substrate intermediate, therefore it should not be assumed that a more acidic catalyst will always lead to improved enantioselectivity .…”
Section: Discussionmentioning
confidence: 74%
“…Synthetic chemists have applied this mode of activation to asymmetric catalysis, where hydrogen bond donors are used in small chiral molecules to impart facial selectivity during catalysis. Recent advancement in this field has been rapid, and a plethora of structurally distinct catalysts, covering a range of approximately 20 p K a units, have been successfully employed. Despite the surge of reports, mechanistic understanding of how subtle changes to catalyst structure affect selectivity is still relatively scarce. Moreover, the influence of catalyst acidity upon reaction outcome, both in terms of rate , and enantioselectivity, remains underinvestigated. This lack of understanding is likely due to the fact that significant structural differences often make the direct comparison of catalysts with different acidity uninformative.…”
Section: Introductionmentioning
confidence: 99%